2020
DOI: 10.1186/s12905-020-00957-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of use of withdrawal for contraception among women in Vietnam

Abstract: Background: Despite its relatively low effectiveness, withdrawal is a common contraceptive practice. In Vietnam, health concerns about hormonal contraception are strong and account for substantial method discontinuation. Given the paucity of evidence on withdrawal, our objective was to identify correlates of using withdrawal among women not desiring pregnancy. Methods: We conducted a secondary analysis of data from a cross-sectional study of sexually-active adult women attending a public hospital in Hanoi, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
1
0
3
Order By: Relevance
“…26 Nguyen ve ark. 'nın 16 çalışmasında da gebelikten kaçınmanın önemi ile geri çekme yöntemi kullanma durumu arasında anlamlı fark olduğu belirtilmiştir. 16 Berber'in 19 çalışmasında, kadınların ideal çocuk sayıları ile yöntemleri arasında istatiksel olarak anlamlı fark saptanmıştır.…”
Section: Gereç Ve Yöntemunclassified
See 2 more Smart Citations
“…26 Nguyen ve ark. 'nın 16 çalışmasında da gebelikten kaçınmanın önemi ile geri çekme yöntemi kullanma durumu arasında anlamlı fark olduğu belirtilmiştir. 16 Berber'in 19 çalışmasında, kadınların ideal çocuk sayıları ile yöntemleri arasında istatiksel olarak anlamlı fark saptanmıştır.…”
Section: Gereç Ve Yöntemunclassified
“…[12][13][14] Bu yöntem, eşler arasında uyum, disiplin ve motivasyon gerektirmektedir. 2,15,16 Uygulama kolaylığı ve maliyetsiz olması nedeni ile Türkiye'de hâlen evli kadınlar arasında en yaygın olarak kullanılan yöntem olan geri çekme, etkisi sınırlı bir yöntemdir. 7,11,[17][18][19] Doğru kullanıldığında emzirmeyi etkilememesi ve her zaman birincil kullanım veya yedek yöntem olarak kullanım için mevcut olması, yöntemin diğer olumlu yönlerindendir.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…These methods continue to be commonly used outside of Africa. Jones et al (2014) found that 33 per cent of people have used the pull-out (withdrawal) method at least once, despite having a failure rate of approximately 20 per cent (Nguyen et al, 2020). However, many people use the withdrawal method in combination, or in rotation with condoms and other effective methods (Jones et al, 2014;Nguyen et al, 2020).…”
Section: Indigenous Contraceptive Methodsmentioning
confidence: 99%